CLARIN-PL: a user centred language technology infrastructure. - Piasecki, Maciej; Dziob, Agnieszka; Janz, Arkadiusz; Kocoń, Jan; Naskrȩt, Tomasz; Oleksy, Marcin; Rudnicka, Ewa; Walkowiak, Tomasz; Wieczorek, Jan; Hwaszcz, Krzysztof (Language Resources & Evaluation, 2025)
The paper presents the development of CLARIN-PL, the Polish node of CLARIN ERIC, an open, pan-European language technology infrastructure for Social Sciences and Humanities. The main challenge for CLARIN-PL was to fill a huge gap in language tools and resources for Polish. Another was to reach out to their potential users—SS&H researchers. This enforced a bidirectional approach: bottom-up, building many LRTs from scratch, and user-centric, going from specific users' needs to in-house applications. Currently, CLARIN-PL offers a full NLP processing pipeline for Polish, a variety of LRTs, and different types of NLP applications. It has attracted a number of users from SS&H, and is also being expanded towards an LTI for business.